Motif dan Makna Berjilbab Mahasiswi Komunikasi Universitas Tadulako Palu - Sitti Murni Kaddi; Enjang Muhaemin (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2020)
This research-based paper aims to find out the motives and meanings of wearing headscarves by the students of Communication Studies at the Faculty of Social and Political Sciences, Tadulako University, Palu. The study uses qualitative research methods, with in-depth interview techniques, and observation, to explore the motives and veiled meanings of the female students. The research uses a phenomenological approach. The results of the study concluded two things. First, the causes of female students wearing headscarves are divided into two, namely the motives of the past and the motives of the future. Purposes of the past are encouraged because of encouragement and advice from parents and family, as well as shar' i motifs based on obligations established by Islam. The future motives underlying the female students to wear the veil are divided into the motivation of wanting to avoid bad things, wanting to control behavior, and wanting to be appreciated. Second, related to self-meaning, the students who wear the hijab interpret it as proof of love for God, and as a service to both parents.Tulisan berbasis penelitian ini bertujuan untuk mengetahui motif dan makna pemakaian jilbab yang dilakukan para mahasiswi Ilmu Komunikasi FISIP Universitas Tadulako Palu. Penelitian menggunakan metode penelitian kualitatif, dengan teknik wawancara mendalam, dan observasi, dengan tujuan menggali motif, dan makna berjilbab para mahasiswi. Penelitian menggunakan pendekatan fenomenologis. Hasil penelitian menyimpulkan dua hal. Pertama, motif mahasiswi memakai jilbab terbagi menjadi dua, yaitu motif masa lalu dan motif masa depan. Motif masa lalu didorong karena dorongan dan nasehat dari orang tua dan keluarga, serta motif syar’i yang didasarkan pada kewajiban yang ditetapkan Islam. Adapun motif masa depan yang mendasari mahasiswi menggunakan jilbab terpilah pada motif ingin menghindari hal-hal buruk, ingin mengontrol tingkah laku, dan ingin dihargai. Kedua, berkaitan dengan makna diri, para mahasiswi pemakai jilbab memaknainya sebagai bukti sayang kepada Allah, dan sebagai bakti kepada kedua orang tua.